1140. Impact of a Rapid Molecular Bloodstream Diagnostic Test on Optimal Antibiotic Use in Infants. (4th December 2021) - Norman, Savanah; Burton, Alexandra; Mumphrey, Christy; Joslyn, Peter; Cook, Gregory
Abstract: Background: Rapid molecular bloodstream diagnostics have been shown to decrease time-to-optimal antibiotic therapy in adult and pediatric patients. The purpose of the study was to compare the time-to-optimal antimicrobial therapy both pre-and post- implementation of rapid diagnostic testing in infants. Methods: This was a single-center quasi-experimental study conducted from December 2018 to December 2020 at Children's Hospital New Orleans. A rapid, multiplex polymerase chain reaction bloodstream diagnostic was implemented in January 2019. Antimicrobial Stewardship performed a daily review of all antimicrobials during both periods and made recommendations when necessary. The primary outcome was the difference in time-to-optimal therapy. Secondary outcomes included time-to-effective therapy, 30-day all-cause mortality rate, 30-day recurrent bacteremia rate, and time-to-microbiologic clearance. Patients were excluded if they had an unrelated concomitant infection, withdrawal of care before the result, bacteria not identified by the panel, or were over 6 months of age. Results: Thirty-five and forty-three patients met inclusion criteria pre-and post-implementation. The median post-natal age was 2 months and median PRISM score was 12 in both groups. Median time-to-optimal therapy was 53.1 hours in the pre-intervention and 24.4 hours in the post-intervention group (-28.7 hours, P = 0.03). Median time-to-effective therapy was 0 and 1.4 hours, respectively (+1.4 hours, P = 0.02). There was no significant difference in 30-day all-cause mortality (3 vs. 4 patients, P = 0.62), 30-day recurrent bacteremia (0 vs. 2 patients, P = 0.2), or microbiologic clearance (37.3 vs. 26.2 hours, P = 0.09). Conclusion: Implementation of a rapid, multiplex bloodstream diagnostic lead to a significant decrease in time-to-optimal antibiotic therapy in infants when compared to standard microbiological techniques. Disclosures: All Authors : No reported disclosures